Howards end - Forster, E. M. (Edward Morgan), 1879-1970. (London : Hodder & Stoughton, 2010)
An old country home in Hertfordshire called Howards End becomes the object of an inheritance dispute between the Wilcox family and the Schlegel sisters.
Adult.
Adult
Keywords: Inheritance and succession -- Fiction; Social conflict -- England -- Fiction; Inheritance and succession -- Fiction; Social conflict -- Fiction; England -- Social life and customs -- Fiction; England -- Social life and customs -- Fiction